Gambaran Karakteristik Pasien Fibroadenoma Mammae di RSD Gunung Jati Cirebon Periode 2022-2024 - Claudia Valensia Oktaviana; Yukke Nilla Permata; Asih Ambarsari (Malahayati Nursing Journal, 2026)
ABSTRACT Fibroadenoma mammae (FAM) was identified as the most common breast lump occurring in young women. FAM was characterized by a firm, rubbery, well-defined, non-tender, and mobile mass. According to data from KEMENKES RI in 2019, there were 28,910 reported cases of FAM, with the highest prevalence found in West Java Province, total 6,109 cases. This study aimed to describe the characteristics of patients diagnosed with FAM at Gunung Jati Cirebon Hospital during the 2022–2024 period, based on age, lump location, number, size, and the presence of pain. A descriptive observational design was utilized. Secondary data were obtained from medical records of patients who met the inclusion criteria. A total sampling technique was applied, and 116 patient records were analyzed. The majority of FAM patients were in the young adult age group (20–44 years), accounting for 57.8%. Most lumps were located in the right breast (51.7%). Solitary lumps were found in 90.5% of cases, with a typical size of 1–5 cm (62.1%). Pain was reported by 63.8% of the patients. FAM cases at Gunung Jati Cirebon Hospital most frequently occurred among young adult women. The typical presentation involved right-sided, solitary lumps, sized 1–5 cm, and accompanied by pain. These findings may serve as a foundation for improving early detection strategies and enhancing public education regarding FAM. Keywords: Fibroadenoma Mammae, Patient Characteristics, Age, Pain, Breast. ABSTRAK Fibroadenoma mammae (FAM) merupakan benjolan payudara yang paling sering terjadi pada wanita usia muda. FAM memiliki karakteristik berupa benjolan padat, kenyal, batas tegas, tidak nyeri, dan dapat digerakkan. Berdasarkan data KEMENKES RI tahun 2019 angka kejadian FAM sebanyak 28.910 kasus, dengan prevalensi tertinggi di provinsi Jawa Barat sebanyak 6.109 kasus. Mengetahui gambaran karakteristik pasien FAM di RSD Gunung Jati Cirebon periode 2022–2024 berdasarkan usia, lokasi, jumlah, ukuran, dan nyeri. Penelitian ini menggunakan desain deskriptif observasional dengan pengambilan data sekunder dari rekam medis pasien FAM yang memenuhi kriteria inklusi. Teknik sampling yang digunakan adalah total sampling, dengan jumlah sampel sebanyak 116 pasien. Sebagian besar pasien FAM berada pada usia dewasa muda (20–44 tahun) sebesar 57,8%. Lokasi benjolan terbanyak terdapat pada payudara dextra (51,7%). Mayoritas pasien memiliki benjolan soliter (90,5%) dengan ukuran umum 1–5 cm (62,1%). Sebanyak 63,8% pasien mengeluhkan adanya nyeri pada benjolan.  FAM pada pasien di RSD Gunung Jati Cirebon paling banyak terjadi pada usia dewasa muda, lokasi benjolan di payudara dextra, jumlah benjolan soliter, ukuran benjolan 1-5 cm, dan disertai nyeri. Data ini dapat menjadi dasar dalam peningkatan deteksi dini dan edukasi masyarakat mengenai FAM. Kata Kunci: Fibroadenoma Mammae, Karakteristik Pasien, Usia, Nyeri, Payudara.